The German "culpa in contrahendo" - Ick, Harald (Department of Private Law, 2021)
In German law the contractual liability of the debtor requires an obligation, this is expressed within the German civil code which formulates 'an obligatory relationship'. For this reason, any fault (Verschulden) committed before or during the conclusion of a contract, can only be an unlawful act, in the circumstances of the law of delict. However certain problems in the law of delict arise, such as the enumeration principle, exculpatory proof, burden of proof and prescription times. These problems caused unsatisfactory results in special constellations since the German Civil Code (BGB) was enacted in 1900. Therefore, the courts and the legal writers i.n addition to the written code, and without consent or refusal by the legislator, developed the concept of 'culpa in contrahendo' as 'fault during the negotiations of a contract' (Verschulden bei Vertragsverhandlungen).